1990
DOI: 10.1128/mcb.10.9.4590
|View full text |Cite
|
Sign up to set email alerts
|

A novel small-subunit ribosomal protein of yeast mitochondria that interacts functionally with an mRNA-specific translational activator.

Abstract: Mitochondrial translation of the mRNA encoding cytochrome c oxidase subunit III (coxIII) specifically requires the action of three position activator proteins encoded in the nucleus of Saccharomyces cerevisiae. Some mutations affecting one of these activators, PET122, can be suppressed by mutations in an unlinked nuclear gene termed PET123. PET123 function was previously demonstrated to be required for translation of all mitochondrial gene products. We have now generated an antibody against the PET123 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…Strains were CAB30 and SN33. (McMullin et al, 1990;Haffter et al, 1991;Haffter and Fox, 1992) and interactions between of Nam1p and Rpo41p (mitochondrial RNA polymerase) (Rodeheffer et al, 2001) were reported previously. Two-hybrid and genetic interactions among Pet54p, Pet122p, and Pet494p were reported previously (Brown et al, 1994;Wiesenberger et al, 1995). without eliminating respiratory complex formation, by in vivo expression of chimeric mRNAs containing 5Ј-UTLs and coding sequences derived from different respiratory complex genes (Mü ller et al, 1984;Fox, 1986, 1988;Poutre and Fox, 1987;Rö del and Fox, 1987;Mulero and Fox, 1993b;Manthey and McEwen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Strains were CAB30 and SN33. (McMullin et al, 1990;Haffter et al, 1991;Haffter and Fox, 1992) and interactions between of Nam1p and Rpo41p (mitochondrial RNA polymerase) (Rodeheffer et al, 2001) were reported previously. Two-hybrid and genetic interactions among Pet54p, Pet122p, and Pet494p were reported previously (Brown et al, 1994;Wiesenberger et al, 1995). without eliminating respiratory complex formation, by in vivo expression of chimeric mRNAs containing 5Ј-UTLs and coding sequences derived from different respiratory complex genes (Mü ller et al, 1984;Fox, 1986, 1988;Poutre and Fox, 1987;Rö del and Fox, 1987;Mulero and Fox, 1993b;Manthey and McEwen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Some T factors may act by unmasking the initiation codon of their target mRNA, sequestered into a secondary structure (Stampacchia et al, 1997;Klinkert et al, 2006;Schwarz et al, 2007). Alternatively, T factors may recruit the translation machinery, but their affinity for components of this machinery remains to be documented in most cases (however, see McMullin et al, 1990;Haffter et al, 1991;Haffter and Fox, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that the yeast mitoribosome consists of a core structure of homologous components, responsible for carrying out central steps of protein synthesis common to both eubacteria and mitochondria, and an additional set of proteins with a more specialized function in mitochondrial protein synthesis [19]. In this respect it is worth noting that none of the three mitoribosomal proteins (PET123, MRP1, MRP17) found to functionally interact with the unique mRNA-specific translational activator PET122 (see below) displays homology to other known ribosomal proteins [20][21][22].…”
Section: The Mitochondrial Ribosomementioning
confidence: 99%
“…Three of these suppressors have turned out to be mutations in genes encoding proteins of the small mitoribosomal subunit [20][21][22]80], thus strongly suggesting that PET122 activates translation of the COX3 mRNA via an interaction with this ribosomal subunit. The fourth nuclear gene isolated in this screen, PET12 7, differs from the previous three in that its function is not absolutely required for mitochondrial gene expression [21].…”
Section: Mrna-specific Translational Activatorsmentioning
confidence: 99%